Temperature dynamics of the microdroplet fraction of metal plasma in plasma-optical devices with fast electrons - Goncharov, A.A.; Litovko, I.V.; Ryabtsev, A.V. (Problems of Atomic Science and Technology, 2023)
The computer simulation of a plasma filter with fast electrons shows that the main source of droplet heating is thermal electrons, while the role of fast electrons is reduced mainly to transferring energy to slow electrons. The processes of drop charging in the presence of an electron beam and the effective emission of electrons due are also considered. Комп’ютерне моделювання плазмового фільтра зі швидкими електронами показує, що основним джерелом нагріву краплі є теплові електрони, тоді як роль швидких електронів зводиться, в основному, до передачі енергії повільним електронам. Розглянуто також процеси заряджання краплі в присутності електронного пучка та ефективну емісію електронів за рахунок цього.